Criminal Acts in Completing Early Marriage Requirements: Tuku Umur Practices in Islamic Communities in Central Java, Indonesia - Ismawayati, Any; Ngazizah, Inna Fauziatal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
The goal of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 Concerning Marriage is to reduce the high rate of early marriage because it violates the rights and development of children. In fact, the rate of child marriage in Indonesia is rising. This circumstance raises the question of whether or not the current regulations are effective. This study seeks to determine the extent to which the Islamic community in Central Java understands the significance of the age limit for marriage. This study also determines why the Islamic community in Central Java prefers "Tuku umur" to fulfill the requirements for early marriage and to determine whether "Tuku umur" constitutes a criminal act. This research employed a juridical-sociological approach with complementary data, namely the distribution of information through interviews with informants in response to several question indicators indicated in the discussion. According to the findings of this study, the Islamic community of Central Java has not fully grasped the significance of the age limit for marriage; hence they tend to disregard these regulations. This study reveals that some Muslim communities in Central Java prefer to practice the "Tuku umur" to fulfill the conditions for early marriage since it is simpler than seeking a marriage dispensation. In addition, the findings of this study imply that "Tuku umur" is a criminal act because it contains falsified data. Additionally, Tuku umur is a bribery offense, one of the sorts of corruption.